REGULATORY AND LEGAL CHALLENGES OF SHARIA PEER-TO-PEER LENDING IN INDONESIA (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2024)
Peer-to-peer (P2P) lending is a financial platform that connects lenders directly with borrowers without going through traditional financial intermediaries. Sharia P2P lending applies sharia principles in its transactions. Even though sharia P2P lending in Indonesia has increased in recent years, regulatory and legal challenges still hamper its growth. This research aims to analyze the regulatory and legal challenges faced by Sharia P2P lending in Indonesia and provide policy recommendations to overcome them. This research uses qualitative methods by conducting a literature review of sharia P2P lending regulations in Indonesia and in-depth interviews with regulators, sharia P2P lending practitioners, and academics. The research results show that the main challenges faced are regulatory uncertainty, the need for a Sharia legal framework for P2P lending, and the regulator's lack of understanding of the Sharia-based P2P lending business model. The proposed policy recommendations include establishing a comprehensive and integrated Sharia P2P lending regulatory framework, preparing legally binding Sharia fatwas, and increasing regulators' literacy and understanding of the digital Sharia financial sector. The policy implications of this research can provide input for regulators and practitioners in developing a healthy and sustainable Sharia P2P lending ecosystem in Indonesia.